2011
DOI: 10.1091/mbc.e11-03-0207
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation within the SH3 domain regulates CAS subcellular localization, cell migration, and invasiveness

Abstract: Crk-associated substrate (CAS) Tyr-12 phosphorylation has an important role in ligand binding, CAS localization, turnover of adhesion structures, migration, and invasiveness. CAS Tyr-12 phosphorylation thus possibly represents a novel regulatory mechanism by which CAS-mediated signaling could trigger different cellular responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 47 publications
3
61
0
Order By: Relevance
“…Accordingly, phosphorylated Cas levels in FAs increased approximately 3-fold when Cul5 expression was inhibited, especially in FAs in the front 6 µm of the cell (Figure 5—figure supplement 3). Since Cas exchanges rapidly between the cytosol and FAs (Janostiak et al, 2011; Machiyama et al, 2014), the increase in pYCas in FAs could be secondary to the increased Cas in the cytosol. Moreover, the chronic increase in pYCas in adhesions could accelerate adhesion turnover regardless of whether SOCS6 targets Cas in the cytosol or in FAs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, phosphorylated Cas levels in FAs increased approximately 3-fold when Cul5 expression was inhibited, especially in FAs in the front 6 µm of the cell (Figure 5—figure supplement 3). Since Cas exchanges rapidly between the cytosol and FAs (Janostiak et al, 2011; Machiyama et al, 2014), the increase in pYCas in FAs could be secondary to the increased Cas in the cytosol. Moreover, the chronic increase in pYCas in adhesions could accelerate adhesion turnover regardless of whether SOCS6 targets Cas in the cytosol or in FAs.…”
Section: Resultsmentioning
confidence: 99%
“…Removal of Cas by this mechanism would be expected to open up sites in the FA where other Cas molecules could bind. It is known that most of the Cas in a FA exchanges with Cas from the cytosol with a very rapid (~20 s) rate constant (Janostiak et al, 2011; Machiyama et al, 2014). It seems remarkable that ubiquitination and degradation of pYCas would affect the kinetics of FA disassembly if new Cas molecules could replace degraded molecules with such speed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it was shown that the interaction of the CAS-SH3 domain with its substrates can be regulated by phosphorylation on Tyr1291213. This enables dynamically regulated changes in CAS targeting to focal adhesions, which might be critical for proper subsequent signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Although post-translational modification of conventional SH3 domains by tyrosine phosphorylation has been documented, for example for Btk, Abl and recently for the CAS/BCAR1 SH3 domain, in contrast to the Crk SH3C, this occurs on the conserved tyrosine in the hydrophobic ligand binding pocket and thereby reduces the affinity of the SH3 domain for its ligands [14][15][16][17][18]. The SH3 domain of CAS/BCAR1, a focal adhesion protein shown to be associated with resistance to anti-estrogens in breast cancer, is phosphorylated on this tyrosine in Src-transformed cells [19].…”
Section: Introductionmentioning
confidence: 99%